Physicochemical stability of human insulin 1 I.U./mL infusion solution in 50 mL polypropylene syringes - Mohr André; Erdnüß Frank; Krämer Irene (De Gruyter, 2021)
The objective of this study was to investigate the physicochemical stability of human insulin 1 I.U./mL injection solutions (Insuman® Rapid) diluted with 0.9% NaCl solution in 50 mL disposable three-piece polypropylene syringes and stored refrigerated or at room temperature.